Specialization in the medial temporal lobe for processing of objects and scenes - Lee, Andy C.H.; Buckley, Mark J.; Pegman, Sarah J.; Spiers, Hugo; Scahill, Victoria L.; Gaffan, David; Bussey, Timothy J.; Davies, R. Rhys; Kapur, Narinder; Hodges, John R.; Graham, Kim S. (Hippocampus, 2005)
There has been considerable debate as to whether the hippocampus and perirhinal cortex may subserve both memory and perception. We administered a series of oddity tasks, in which subjects selected the odd stimulus from a visual array, to amnesic patients with either selective hippocampal damage (HC group) or more extensive medial temporal damage, including the perirhinal cortex (MTL group). All patients performed normally when the stimuli could be discriminated using simple visual features, even if faces or complex virtual reality scenes were presented. Both patient groups were, however, severely impaired at scene discrimination when a significant demand was placed on processing spatial information across viewpoint independent representations, while only the MTL group showed a significant deficit in oddity judgments of faces and objects when object viewpoint independent perception was emphasized. These observations provide compelling evidence that the human hippocampus and perirhinal cortex are critical to processes beyond long‐term declarative memory and may subserve spatial and object perception, respectively. ©2005 Wiley‐Liss, Inc.